Evaluation of Static Friction of Polycrystalline Ceramic Brackets after Conditioning with Different Powers of Er:YAG Laser - Valiollah Arash; Saeed Javanmard; Zeinab Eftekhari; Manouchehr Rahmati-Kamel; Mohammad Bahadoram (International Journal of Dentistry)
This research aimed to reduce the friction between the wire and brackets by Er:YAG laser. To measure the friction between the wires and brackets in 0° and 10° of wire angulations, 40 polycrystalline ceramic brackets (Hubit, South Korea) were divided into 8 study groups and irradiated by 100, 200, and 300 mj/s of Er:YAG laser power. Two groups of brackets were not irradiated. The friction between the wires and brackets was measured with universal testing machine (SANTAM) with a segment of .019 × .025 SS wire pulled out of the slot of bracket. ANOVA and t-test were used for analyzing the results. To evaluate the effect of the laser on surface morphology of the bracket, SEM evaluations were carried out. The mean frictional resistances between the brackets and wires with 0° of angulation by increasing the laser power decreased compared with control group, but, in 10° of angulation, the friction increased regardless of the laser power and was comparable to the friction of nonirradiated brackets. Furthermore, with each laser power, frictional resistance of brackets in 10° of angulation was significantly higher than 0° of angulation. These results were explained by SEM images too.